Structural Performance Tests of Down Scaled Composite Wind Turbine Blade using Embedded Fiber Bragg Grating Sensors - Kim, Sang-Woo; Kim, Eun-Ho; Rim, Mi-Sun; Shrestha, Pratik; Lee, In; Kwon, Il-Bum (International journal of aeronautical and space sciences, 2011)
In this study, the structural performance tests, i.e., static tests and dynamic tests of the composite wind turbine blade, were carried out by using the embedded fiber Bragg grating (FBG) sensors. The composite wind turbine blade used in the test is the 1/23 scale of the 750 kW composite blade. In static tests, the deflections along the blade were evaluated. Evaluations were carried out with simple beam theory and quadratic fitting method by using the embedded FBG sensors to predict the structural behavior with respect to the load. The deflections were compared to those obtained from the laser displacement sensor and electric strain gauges. They showed good agreement. Modal tests were performed to investigate the dynamic characteristics using the embedded FBG sensors. The natural frequencies obtained from the FBG sensors corresponding to the nine mode shapes of the blade were compared to those from the laser Doppler vibrometer. They were found to be consistent with each other. Therefore, it is concluded that the embedded FBG sensors have a great capability for measuring the structural performances of the composite wind turbine blade when structural performance tests are carried out. KCI Citation Count: 1